MRI-based high-precision irradiation in an orthotopic pancreatic tumor mouse model - Dobiasch, Sophie; Kampfer, Stefanie; Habermehl, Daniel; Duma, Marciana Nona; Felix, Klaus M.; Strauß, Albert; Schilling, Dieter; Wilkens, Jan; Combs, Stephanie (Strahlentherapie und Onkologie, 2018)
Recently, imaging and high-precision irradiation devices for preclinical tumor models have been developed. Image-guided radiation therapy (IGRT) including innovative treatment planning techniques comparable to patient treatment can be achieved in a translational context. The study aims to evaluate magnetic resonance imaging/computed tomography (MRI/CT)-based treatment planning with different treatment techniques for high-precision radiation therapy (RT).
Gesehen am 26.03.2020